Amperometric detection of triclosan with screen-printed carbon nanotube electrodes modified with Guinea Grass (Panicum maximum) peroxidase - Orduz Navas, Angie Estefany (2019)
Triclosan is a compound with antimicrobial activity broadly used in consumer products. Because of its well documented toxicity, the amount of triclosan present in different products needs to be tightly controlled. This paper outlines a new amperometric sensor for triclosan detection consisting of a screen-printed carbon nanotube electrode (SPCNE) modified w ith Guinea grass peroxidase (GGP). The GGP-modified S PCNE was a ble t o d etect an enhanced electrochemical response of triclosan, unlike the bare SPCNE. The cyclic voltammograms of the GGP-modified SPCNE in a solution of potassium ferrocyanide showed an increase in the current values and linearity between scan rates and oxidation peak currents, suggesting a surface controlled process. The GGP-modified SPCNEs howed an excellent electrocatalytic activity to triclosan oxidation, at a redox potential of 370 mV, in the presence of hydrogen peroxide, exhibiting a linear response between 20 mM to 80 mM and a detection limit of 3 µM. This new amperometry system, based on carbon nanotubes integrated with GGP, becomes a potential tool for environmental analysis and food quality control.